Pemberdayaan Masyarakat melalui Digitalisasi Berbasis Potensi Desa di Desa Niramesi Kecamatan Wolowaru Kabupaten Ende - Djata, Baltasar Taruma (LPPM Universitas Flores, 2022)
We should know in detail the characteristics, strengths and weaknesses of the village, so that village development can be in accordance with the potential of the village to be sold. In this case, local residents can participate in village development, so that they can be used as subjects in the development of their village. One of the efforts made is by way of community empowerment. The method of implementation is to coordinate with the Head of Niramesi Village to obtain an overview of the profile and geographical conditions and demographics of the village, then conduct a survey to each hamlet to determine the state and digital capabilities of the community members, the next stage is to create an e_Mail account for the community and the technical stage of socialization is to carry out digital literacy. Through digital literacy activities, it can open insight and knowledge for the residents of Niramesi Village, Wolowaru District to build digital literacy and use digital technology appropriately. The public can take advantage of digital means for promotion and marketing of brands or products through digital media and digital media can reach a wider and cost-efficient market.